2015
DOI: 10.1016/j.aucc.2014.10.044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a 2-tier rapid response system on patient outcome and staff satisfaction

Abstract: The 2-tier RRS was accessed by staff to assist with care of deteriorating patients in a large, tertiary hospital. High levels of satisfaction have been reported by clinical staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…Table 1 provides a summary of the included studies. Of the 23 studies included in the review, 11 were qualitative (Rihari-Thomas et al, 2017;Petersen et al, 2017;McGaughey et al, 2017;Martland et al, 2016;Liaw et al, 2017;Kitto et al, 2015;Hart et al, 2016;Elliott et al, 2015;Donohue and Endacott, 2010;Currey et al, 2018;Burns et al, 2018), 8 were quantitative research studies (Davies et al, 2014;Douglas et al, 2016: Fox andElliott, 2015;Heal et al, 2017;Liaw et al, 2016;Ludikhuize et al, 2011;Osborne et al, 2016;Rattray et al, 2011) and 4 were of a mixed methodology (Aitken et al, 2015;Cherry and Jones, 2015;Shearer et al, 2012;Smith and Aitken, 2016).…”
Section: Characteristics Of Sources Of Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 provides a summary of the included studies. Of the 23 studies included in the review, 11 were qualitative (Rihari-Thomas et al, 2017;Petersen et al, 2017;McGaughey et al, 2017;Martland et al, 2016;Liaw et al, 2017;Kitto et al, 2015;Hart et al, 2016;Elliott et al, 2015;Donohue and Endacott, 2010;Currey et al, 2018;Burns et al, 2018), 8 were quantitative research studies (Davies et al, 2014;Douglas et al, 2016: Fox andElliott, 2015;Heal et al, 2017;Liaw et al, 2016;Ludikhuize et al, 2011;Osborne et al, 2016;Rattray et al, 2011) and 4 were of a mixed methodology (Aitken et al, 2015;Cherry and Jones, 2015;Shearer et al, 2012;Smith and Aitken, 2016).…”
Section: Characteristics Of Sources Of Evidencementioning
confidence: 99%
“…The methods of the Quantitative studies involved surveys in five studies (Davies et al, 2014;Douglas et al, 2016;Fox and Elliott, 2015;Osborne et al, 2016: Rattray et al, 2011 and trials in the three other studies (Ludikhuize et al, 2011;Heal et al, 2017;Liaw et al, 2016). The methods used in the mixed methods studies included pre and post intervention, evaluation and interviews with clinicians (Aitken et al, 2015), data collected from questionnaires and focus groups (Cherry and Jones, 2015) and point in times audits and interviews with staff (Shearer et al, 2012;Smith and Aitken, 2016).…”
Section: Characteristics Of Sources Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…However, another meta-analysis and the only multicenter randomized control trial to date have not found strong evidence to support the effectiveness of rapid response systems [ 2 , 3 ]. In many of these studies, the quality of the rapid response system as a systematic intervention itself has not been evaluated [ 17 20 ]. Previous reviews of rapid response systems have treated rapid response systems as if they were of equal quality and had comparable operating procedures [ 2 , 17 , 19 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Technical aspects such as quality cardiopulmonary resuscitation (CPR) 4 and adherence to advanced cardiovascular life support protocols 5 have been linked to better outcomes, but less is known about how nontechnical factors such as team leadership and communication may improve survival. [6][7][8][9][10][11] Evidence from cardiac arrest simulation literature suggests that the absence of leadership and of clearly defined roles is associated with negative outcomes. [7][8][9][10][11][12] As part of a performance improvement project, we deconstructed code-team activations at our center and revised our process to include specific interventions targeted at providing clear roles for providers and improving our leadership structure.…”
mentioning
confidence: 99%